Lukang : commerce and community in a Chinese city - DeGlopper, Donald R. (Donald Robert), 1942- (SUNY series in Chinese local studies., 1995)
"Based on anthropological fieldwork in Lukang, an old seaport in Taiwan, this book examines the city's history, economic structure, and social organization. It addresses such matters as an annual rock fight between the city's major clans, the way votes are bought in local elections, and why the inhabitants of a fairly large industrial and commercial city describe it as a cozy community where everyone knows everyone else. The book uses the framework of a community study to address such large questions as the adequacy of Confucianism as model for Chinese society, the nature of Chinese social organization beyond the realm of the family and kinship, and the structure of Chinese society generally and the city of Lukang specifically and the ways the members of that society talk about their society and their own places in it."--Jacket